The impact of sensorial-motor sequels in the autonomy and independence of patients affected by Cerebrovascular Accidents (CVA) - Debora Sanchez Pedrolo; Carina Tárzia Kakihara; Margarida Maria de Almeida (O Mundo da Saúde)
Cerebrovascular Accidents (CVA) is the second cause of deaths in the world and one of the most common permanent causes of sequels, in a scale corresponding to the gravity of the injury. The aim of this work was to evaluate, under the perspective of the after-CVA patients, the impact of sequels in their autonomy and functional independence. It is a qualitative study, with semistructured interviews of 4 subjects, both male and female, with ages from 44 to 71 years. Data were analyzed by the technique of thematic content analysis and lead to the emergence of four categories: immediate help and hospital treatment; the impact of sequels in the autonomy and independence; ways to face the limitations; and the role of physiotherapy in rehabilitation. The limitations sequels cause interfere in daily activities, although they are not impeditive, thanks to the adaptations developed.